Harvesting thermoelectric energy from hybrid solar PV system / Muhamad Aiman Hafiz Muhamad Ikbal - Muhamad Ikbal, Muhamad Aiman Hafiz (2025)
The integration of Thermoelectric Generators (TEGs) with photovoltaic (PV) systems offers a promising approach to enhance energy conversion efficiency by recovering waste heat. This study evaluates the performance of a hybrid PV-TEG system compared to a standalone PV system over a 30-day period. The hybrid system achieved an average efficiency of 69.56%, surpassing the standalone system's 68.53%. These results significantly exceed efficiencies reported in literature, where standalone PV and hybrid PV-TEG systems achieved 11.6% and 14%, respectively. The improvements observed in this study may be attributed to optimized system design, advanced materials, and favorable testing conditions. Future work will focus on validating these findings under diverse environmental conditions, improving TEG material efficiency, and exploring additional hybrid configurations. This research highlights the potential of Hybrid PV- TEG Systems to revolutionize renewable energy by providing sustainable and highly efficient solutions for global energy needs.